Exploring a New ExpAce: The Complementarities between Experimental Economics and Agent-based Computational Economics - Contini, Bruno; Leombruni, Roberto; Richiardi, Matteo (IDEAS Working Paper Series from RePEc, 2006)
What is the relationship, if any, between Experimental Economics and Agent-based Computational Economics? Experimental Economics (EXP) investigates individual behaviour (and the emergence of aggregate regularities) by means of human subject experiments. Agent-based Computational Economics (ACE), on the other hand, studies the relationships between the micro and the macro level with the aid of artificial experiments. Note that the way ACE makes use of experiments to formulate theories is indeed similar to the way EXP does. The question we want to address is whether they can complement and integrate with each other. What can Agent-based computational Economics give to, and take from, Experimental Economics? Can they help and sustain each other, and ultimately gain space out of their restricted respective niches of practitioners? We believe that the answer to all these questions is yes: there can be and there should be profitable "contaminations" in both directions, of which we provide a first comprehensive discussion.